Gluconic Acid Production by Using Recombinant Escherichia coli Waksman pqq+ Cells with a Novel Approach from Biomass Sources - Gul, Abdulkadir; Tanyildizi, Muhammet Saban (Springer, 2024)
Gluconic acid (GA) is widely used in the pharmaceutical, food, detergent, textile, leather, and concrete industries. However, cost-effective and high-yield production of GA remains a challenge. Due to currently high raw material inputs of GA, various alternative carbohydrate sources are being investigated. Sucrose is one of the cost-effective biomass sources that can be used as feedstock. The most common industrial production of GA is based on wild-type bacteria and fungi, but there are many problems with this production. This study aimed to optimize the production of GA from glucose produced by hydrolysis of sucrose using recombinant E. coli Waksman (W) pqq(+) strain. After sucrose was enzymatically hydrolyzed, significant medium components for GA production were determined as glucose, calcium carbonate (CaCO3), peptone, and ammonium phosphate ((NH4)(3)PO4) using Placket-Burman Design (PBD). Detailed optimization of the medium components that are significant in GA production was carried out using central composite design (CCD), and optimum values of the independent variables examined in maximum GA production (93.5 +/- 2.95 g/L) were determined as glucose 95, CaCO3 25, peptone 2, and (NH4)(3)PO4 1.13 (g/L). Using results obtained in the Erlenmeyer experiments, GA production in the bioreactor was investigated by CCD. The maximum GA efficiency (3.20 +/- 0.15 g/L. h) was obtained under conditions where the air supply rate was 10.82 L/min, stirring speed was 656.87 rpm, and CaCO3 concentration was 16.90 g/L. In conclusion, it has been shown that GA can be produced with a high yield with this novel approach using a recombinant strain for GA production from sucrose.
Keywords: E. coli Waksman pqq(+); Gluconic acid; Central composite design; Biomass sources